A fully autonomous power management interface for frequency up-converting harvesters using load decoupling and inductor sharing. (November 2015) - Tom, M; Paul, O; Galchev, T
Abstract: This paper presents the design and simulation results of a self-starting electrical interface circuit for Parametric Frequency Increased Generator (PFIG) vibrational energy harvesters. A significant challenge with these types of harvesters is the ring down of the transducer, introducing an exponential decrease in efficiency when interfaced with standard passive rectifiers. This work aims to address these challenges by interfacing a standard active rectifier to a buck-boost stage in order to decouple the load and always provide an optimal impedance to the transducer. Because PFIG harvesters have two outputs, an inductor sharing technique allows the hardware to be reused. The active buck-boost power management circuit is designed for XFAB's 0.35 μm 2P5M CMOS process. It can provide an efficiency between 75% - 93% for input voltages in the range of 0.5 - 2 V, reaching its maximum efficiency at 1.8 V. The active power consumption of the power converter is 800 nW. The system can start from as low as 800 mV of input voltage and 3 μW of input power.